Hydrophilic interaction chromatography : a guide for practitioners - Olsen, Bernard A., 1953-; Pack, Brian W., 1970- (Hoboken, New Jersey : John Wiley & Sons, Inc., 2013)
"This book provides background information, guidance for method development, and a discussion of applications in the field of hydrophilic interaction chromatography (HILIC.) The book serves as a valuable reference tool for scientists confronted with an analysis problem involving polar compounds to determine if HILIC would be a good choice to pursue and helps them in choosing initial experimental conditions. The book gives a detailed description of the HILIC retention mechanisms and specific information regarding application areas spanning a wide range of industries. Topics include: HILIC retention mechanisms, Stationary Phases for HILIC, HILIC Method Development, Pharmaceutical and Other Applications of HILIC, HILIC for Drug Discovery, HILIC in Two-Dimensional Separations"--
"Covers in detail HILIC retention mechanism, including background on the HILIC mode, what differences it from other HPLC modes, and retention mechanisms that can come into play"--
Separation mechanisms in hydrophilic interaction chromatography -- Stationary phases for HILIC -- HILIC method development -- Pharmaceutical applications of hydrophilic interaction chromatography -- Hydrophilic interaction chromatography (HILIC) for drug discovery -- Advances in hydrophilic interaction chromatography (HILIC) for biochemical applications -- HILIC-MS for targeted metabolomics and small molecule bioanalysis -- HILIC for food, environmental, and other applications -- Theory and practice of two-dimensional liquid chromatography separations involving the HILIC mode of separation.
Includes bibliographical references and index.
Print version record.
Keywords: Hydrophilic interaction liquid chromatography; Chirality; Chromatography, Liquid; Hydrophilic interaction liquid chromatography; Liquid chromatography; SCIENCE -- Chemistry -- Analytic; Hydrophilic interaction liquid chromatography; Electronic books